Kemampuan Menemukan Ide Pokok Paragraf Melalui Pendekatan Konstruktivisme Bahasa Indonesia Siswa Kelas V SDN Karangasem - Firdaus, Adella Tiara Bintara Firdaus (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2023)
This classroom action research was conducted on fifth grade students at SDN Karangasem Mojokerto, due to a problem, namely the learning outcomes of Indonesian subjects, especially the ability to find the main ideas of paragraphs, was still low. Through the constructivism approach this problem is tried to be repaired and improved. This study aims to improve the ability to find the main ideas of paragraphs of fifth grade students at SDN Karangasem Mojokerto. This research is Classroom Action Research (CAR). The research design was carried out through 2 cycles with stages namely planning, action, observation, and reflection. Place of research SDN Karangasem Mojokerto. The subjects of this research were the fifth grade students at SDN Karangasem Mojokerto, which consisted of 11 students. Data collection tools in research use several research methods, namely observation, interviews, documentation, tests and field notes. Therefore, the research data was obtained through classroom observations and documentation of the results of the actions taken as well as data about class condition descriptions. Quantitative data were analyzed with descriptive statistics by finding the average value. The results of this study are that after using the constructivism approach it can improve the results of the ability to find the main ideas of paragraphs in the Indonesian language subject at SDN Karangasem Mojokerto. The learning outcomes obtained were an increase in student learning outcomes according to completeness, namely 74. Students who received a completeness score (74) before the study were 3 students (33%), cycle I were 5 students (54.5%), and cycle II as many as 9 students (81.8%). Therefore, it can be concluded that using the constructivism approach can improve the ability to find the main ideas of paragraphs of fifth grade students at SDN Karangasem Mojokerto.